APLIKASI PENGENALAN ALAT FIBER OPTIK MENGGUNAKAN AUGMENTED REALITY - Muhammad Faishol Amrulloh; Muhammad Febriansyah (STMIK YADIKA BANGIL, 2021)
The limitations of recognition of fiber optics tissue tools so that students have difficulty studying the fiber optics network. One way to increase knowledge using Augmented learning media using Augmented Reality. Therefore, this research will make the application of the recognition of a fiber optics device so that students can visualize and combine the real world with the virtual so that students are more ready to take material on fiber optic networks and improve the learning spirit. This application was created using the Marker Base Tracking method to display 3D objects. The research method used is the method of studies and for application development using waterfall. The results of this study build an optical fixed application. The testing was carried out by demonstrating to SMK direct students who tried this app, the students were requested to fill in a questionnaire as a top assessment of the app they had used. The results of the 86% distance testing presenter testing, an effective corner testing in 450-900, 100% camera testing, 50% light presenter testing and the result of the number questionnaire question that concluded that the presenter 81.50% which concluded that the application user equipment application can be optics to help the fiscal network learning network.. Keywords : Augmented Reality, Marker Based Tracking, Waterfall, Unity3D, Fiber Optic